Winds and tides in the mid-latitude Southern Hemisphere upper mesosphere recorded with the Falkland Islands SuperDARN radar - R. E. Hibbins; R. E. Hibbins; M. P. Freeman; S. E. Milan; J. M. Ruohoniemi (Annales Geophysicae, 2011)
Meteor wind data from the first year of operation of the Falkland Islands SuperDARN radar (52° S, 59° W) are used to characterize the atmospheric tides and background winds in the upper mesosphere above the South Atlantic. Strong (>40 m s−1) semidiurnal tides are observed in the winter time and large amplitude (>60 m s−1) bursts of quasi two-day wave activity are seen in January 2011. Data are in good agreement with those presented from the SAAMER meteor radar (54° S, 68° W). Comparison with SuperDARN meteor wind data from a geographically similar Northern Hemisphere site at Goose Bay (53° N 60° W) reveal clear interhemispheric differences especially in the semidiurnal and terdiurnal components of the tides. The winter time amplitudes of the tides are much stronger in the Southern Hemisphere than in the north. Background winds are observed to be significantly more polewards and westwards throughout the year than those predicted by the empirical horizontal wind model HWM07.